Prioritization technique for learning cloud services - Apitchaka Singjai (2018)
© Emerald Group Publishing Limited. Purpose – The purpose of this paper is to propose a combined technique of cumulative voting and numerical assignment to prioritize the services of the learning cloud service. Design/methodology/approach – The approach starts with requirement elicitation, then analyses of the requirements in terms of prioritization and finally classifies the priority of services into groups. Findings – As a result of the case study the requirements of the College of Art Media and Technology students has been classified into three service groups. Originality/value – This combined prioritized techniques can involve learners in the decision making process about learning cloud services utilization in the organizations.